HAM Gene Family and Shoot Meristem Development - Geng, Yuan; Zhou, Yun (Frontiers in Plant Science, 2021)
Land plants develop highly diversified shoot architectures, all of which are derived from the pluripotent stem cells in shoot apical meristems (SAMs). As sustainable resources for continuous organ formation in the aboveground tissues, SAMs play an important role in determining plant yield and biomass production. In this review, we summarize recent advances in understanding one group of key regulators—the HAIRY MERISTEM (HAM) family GRAS domain proteins—in shoot meristems. We highlight the functions of HAM family members in dictating shoot stem cell initiation and proliferation, the signaling cascade that shapes HAM expression domains in shoot meristems, and the conservation and diversification of HAM family members in land plants. We also discuss future directions that potentially lead to a more comprehensive view of the HAM gene family and stem cell homeostasis in land plants.